Influence of macerated fenugreek (Trigonella foenum graecum) oil added to trout feed at the different rates on the Feed Conversion Rate (FCR), body length, blood parameters and Nitroblue Tetrazolium (NBT) values "‹"‹of rainbow trout (Oncorhynchus mykiss Wal - Altinterim, Başar (Cellular and Molecular Biology, 2019)
In this study, 1% and 2% of macerated fenugreek oil was added to the feeds of rainbow trout with an average weight of 25.79 ± 1.5 g. At the end of the study, growth rate, blood parameters and NBT (Nitroblue Tetrazolium) level of rainbow trout were determined. The best feed ratio (FCR) was observed in the control group (0.77). Statistically significant differences were found only in MID values (P<0.05), although there was a numerical increase in all blood parameters. There was no statistically significant difference between NBT levels (P> 0.05). Although the best weight gain was in the control group as in the FCR values, the maximum elongation was measured at D1 and then at D2 (P <0.05). The best survival rate was obtained with 96.66% in D1 while the worst was observed in D2 with 60% (p<0,05).